Specific Features of Material Recognition by the Multi-Energy X-Ray Method; Russian Journal of Nondestructive Testing; Vol. 55, iss. 4 - Osipov S. P. Sergey Pavlovich; Usachev E. Yu. Evgeny Yurjevich; Chakhlov S. V. Sergey Vladimirovich; Shchetinkin S. A. Sergey Aleksandrovich; Osipov O. S. Oleg Sergeevich (2019, 2019)
Title screen